Obstacles to the Realization of Agrarian Reform in Equitable Distribution of Certification - Rahmatiar, Yuniar; Mulyana, Adin; Handito, Angga Putra; Aprilia, Dinda; Melliana, Melliana; Nugraha, Tirta; Ramadhan, Topani (Jurnal Hukum dan Keadilan, 2024)
The Government of Indonesia launched a program to accelerate the Complete Systematic Land Registration (PTSL) in Indonesia, one of which is Cikuntul Village, Tempuran Regency, West Java. This research aims to understand how the Karawang Regency Government’s programs related to PTSL are implemented in Cikuntul Village. This study uses a juridical-empirical approach, which examines legal sanctions or the practical implementation of legal provisions in certain social events. In Cikuntul Village, land registration efforts face challenges due to the lack of awareness among local communities about its importance. Despite having productive land, many landowners do not have land titles, which leads to complications in land transactions and legal disputes. The Karawang Regency Government is prioritizing national initiatives such as PTSL to distribute land certificates and accelerate land redistribution. However, challenges such as delays in surveying and processing documents at ATR offices hinder the issuance of land certificates. In addition, high registration fees, including notary fees and taxes, discourage residents from registering their land.